Quando as janelas est\~ao abertas: Capacidade institucional da Sudene, Sudeco e Sudam na elaboraç\~ao dos planos de desenvolvimento - Luciléia Aparecida Colombo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The objective of this work is to analyze, through the theory of public policies, the Regional Plans for Regional Development developed by the Superintendencies of Development of the Northeast (Sudene), Development of the Amazonia (Sudam) and Development of the Midwest (Sudeco). Secondarily, we analyzed three main aspects inherent to our object: first, the alignment between the plans and the National Regional Development Policy (PNDR); in addition, we will observe the institutional capacity of the superintendencies to formulate and implement the policies described in the regional plans and, finally, we will seek to indicate the diagnoses contained in these plans with respect to the proposed development. Methodologically, the theory of the public policy cycle and the agenda are guiding factors of the present work, which are adequate for the present work. Preliminarily, we can indicate that the regional plans represent important guidelines for the achievement of public policies, but it is necessary to transition from a government agenda to a decision agenda.
Keywords: H11; H77; R58; 330; regional development; public policy; institutional capacity; regional superintendencies